Prevalence of chronic periodontitis cases at the East Selemadeg I Community Health Centre in Tabanan, Bali, January 2024 to March 2025: Prevalensi kasus periodontitis kronis di Puskesmas Selemadeg Timur I Tabanan Bali Januari 2024-Maret 2025 - Janmastami, Ni Putu Acintya; Pratama, I Wayan Agus Wirya; Kusumadewi, Ni Wayan Adi (Makassar Dental Journal, 2025)
Periodontal disease in Indonesia has a case incidence rate of 96.58%, one of which is rapidly developing periodontitis, affecting approximately 10.5-12% of the world's population. Chronic periodontitis is a significant oral health problem in Indonesia, with pre-valence increasing with age. This study explores the prevalence of chronic periodontitis cases at the Dental Clinic of the Selema-deg Timur I Public Health Centre, Tabanan, Bali, using a cross-sectional research design. The data consisted of patient visit re-cords from January 2024 to March 2025, covering 266 patients diagnosed with chronic periodontitis, showing that female pati-ents were more dominant with a prevalence of 56%. Based on age, the 61-65 age group had the highest number of visits (29.32%). It was concluded that there is a relationship between low educational levels and poor oral health awareness, which contributes to the high incidence of periodontitis. For prevention and treatment, procedures such as scaling, root planing, and surgical inter-vention if necessary are recommended.